4(3-5x)=-5(3x+3)

Simple and best practice solution for 4(3-5x)=-5(3x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3-5x)=-5(3x+3) equation:


Simplifying
4(3 + -5x) = -5(3x + 3)
(3 * 4 + -5x * 4) = -5(3x + 3)
(12 + -20x) = -5(3x + 3)

Reorder the terms:
12 + -20x = -5(3 + 3x)
12 + -20x = (3 * -5 + 3x * -5)
12 + -20x = (-15 + -15x)

Solving
12 + -20x = -15 + -15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15x' to each side of the equation.
12 + -20x + 15x = -15 + -15x + 15x

Combine like terms: -20x + 15x = -5x
12 + -5x = -15 + -15x + 15x

Combine like terms: -15x + 15x = 0
12 + -5x = -15 + 0
12 + -5x = -15

Add '-12' to each side of the equation.
12 + -12 + -5x = -15 + -12

Combine like terms: 12 + -12 = 0
0 + -5x = -15 + -12
-5x = -15 + -12

Combine like terms: -15 + -12 = -27
-5x = -27

Divide each side by '-5'.
x = 5.4

Simplifying
x = 5.4

See similar equations:

| 9t-3=15 | | -11=9-5 | | 180=9x+1+8x+9 | | 3m-2n-4=42 | | 4x+6=2.727272 | | 2x+22=3x+2 | | 11=18+7a | | x+20=34 | | 3(z+12)-7z+2=2(19-2z) | | 41/15=4/5r+2-1/2 | | 5x+4(-9x+17)=-27 | | 7y-1=2(y+3-2) | | 2-1(x-1)=13 | | -2(3x+9)+5(2x+3)=-39 | | 6x^2+3x-108=0 | | 2(w+3)-6w=-14 | | 2*6*3= | | =5*8 | | 5+3p=19 | | 4(5x+7)-(3-x)=4 | | 2n-n+5=3 | | 10+3-(8)= | | w+2x-3y+5y=-98 | | 30-9(5x+1)=-24 | | 5m=8-23m | | -(4a-8)=2(a+4) | | -30=-5x-15 | | x+4*3=x+18 | | 33%x+6=12 | | -4n+6=-3n+8+4 | | 30-9(5x+1)=24 | | 4x^2-32x+52=0 |

Equations solver categories